(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Modern young individuals, often referred to as "digital natives," have grown up in an era characterized by pervasive technology, instant communication, and limitless connectivity. This environment has enabled them to establish relationships and communities at an unprecedented real-time pace.